1987
DOI: 10.1159/000116153
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Lactate in Patients with Hepatic Encephalopathy

Abstract: Cerebrospinal fluid (CSF) lactate and pyruvate concentrations were determined in 16 patients with hepatic encephalopathy before and/or after treatment. CSF lactate was significantly increased to 1.92 ± 0.11 mmol/1 in hepatic encephalopathy before the treatment in comparison to 1.40 ± 0.05 mmol/1 in control subjects. In 9 of 11 patients with moderate or stage 2 encephalopathy, CSF lactate levels were below 2 mmol/1. In contrast, in 4 of 5 patients with stage 3–4 encephalopathy, CSF lactate levels were higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Moreover in acute liver failure, therapeutic interventions, such as mild hypothermia and albumin dialysis, have shown to reduce cerebral lactate along with brain edema and the development of severe HE (coma and intracranial hypertension) [24], [27] and [28]. Furthermore, in the setting of CLD, a 1.37-fold increase in lactate in the cerebrospinal fluid has been found in patients with end-stage liver disease and overt/severe HE (grades 3 and 4) [29]. Chronic hyperammonemic rats (induced following 4-week portacaval anastomosis) injected with a toxic dose of ammonia precipitates severe HE (coma), which is accompanied with brain edema and an increase in brain lactate [30] and [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover in acute liver failure, therapeutic interventions, such as mild hypothermia and albumin dialysis, have shown to reduce cerebral lactate along with brain edema and the development of severe HE (coma and intracranial hypertension) [24], [27] and [28]. Furthermore, in the setting of CLD, a 1.37-fold increase in lactate in the cerebrospinal fluid has been found in patients with end-stage liver disease and overt/severe HE (grades 3 and 4) [29]. Chronic hyperammonemic rats (induced following 4-week portacaval anastomosis) injected with a toxic dose of ammonia precipitates severe HE (coma), which is accompanied with brain edema and an increase in brain lactate [30] and [31].…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In agreement with this, a human PET study found no correlation between CMRA and brain glucose utilization, although a correlation between ammonia uptake and changes in brain metabolites on magnetic resonance spectroscopy was observed, indicating some effects of ammonia in vivo. 27 Cerebral metabolites such as lactate have been found to be increased in animal models 8,21 and in cerebrospinal fluid from patients with HE, 22 which may indicate increased glycolysis, but whether increased lactate is a cause or consequence of HE is uncertain. 23 Thus, although we were unable to link the decrease in CMRO 2 to an increase in CMRA, we cannot rule out that ammonia may be involved in the pathogenesis of HE, perhaps through subtle effects on energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mild hypothermia prevents both brain edema and the accumulation of lactate in CSF in ALF. On the other hand, increased brain lactate is a feature that is common to both acute (Hawkins et al, 1973;Holmin et al, 1983) and chronic (Hindfelt et al, 1977;Therrien et al, 1991;Yao et al, 1987) liver failure and brain edema is generally confined to the acute condition. It is conceivable that compensatory mechanisms occur in chronic liver failure, which render the astrocytes less vulnerable to lactate-induced swelling.…”
Section: Discussionmentioning
confidence: 99%